2013
DOI: 10.1037/a0032367
|View full text |Cite
|
Sign up to set email alerts
|

A prescriptive intergenerational-tension ageism scale: Succession, identity, and consumption (SIC).

Abstract: We introduce a novel ageism scale, focusing on prescriptive beliefs concerning potential intergenerational tensions: active, envied resource Succession, symbolic Identity avoidance, and passive, shared-resource Consumption (SIC). Four studies (2,010 total participants) developed the scale. EFA formed an initial 20-item, three-factor solution (Study 1). The scale converges appropriately with other prejudice measures and diverges from other social control measures (Study 2). It diverges from anti-youth ageism (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
171
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(192 citation statements)
references
References 29 publications
18
171
1
2
Order By: Relevance
“…Similarly, Benton et al (2007) found various associations between different dimensions of aging anxiety and fear of death. In addition, North and Fiske (2013) recently suggested (North & Fiske, 2013) a new instrument which assesses ageism through three different factors (consumption, succession, and identity). These directions are now open to further exploration following the current validation of the basic model.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Benton et al (2007) found various associations between different dimensions of aging anxiety and fear of death. In addition, North and Fiske (2013) recently suggested (North & Fiske, 2013) a new instrument which assesses ageism through three different factors (consumption, succession, and identity). These directions are now open to further exploration following the current validation of the basic model.…”
Section: Discussionmentioning
confidence: 99%
“…3 The survey was financed by the Polish Ministry of Science and Higher Education within a doctoral research grant. 4 Previous measures of ageism included: the Attitudes Towards Old People Scale (Kogan 1961); the Fraboni Scale of Ageism (Fraboni et al 1990) measuring the affective component of ageism; the Palmore Ageism Survey (Palmore 2001); a prescriptive ageism scale (North and Fiske 2013) focusing on prescriptive beliefs concerning potential intergenerational conflicts. Most of these tools measure the cognitive and affective dimensions of ageism and are not designed to study workplace discrimination.…”
Section: Methodsmentioning
confidence: 99%
“…These three elements are the most obvious empiricist characteristics in ageism definitions. Accuracy resulting from empiricist considerations has provided the research field with validated scales to assess ageism (e.g., Lassonde et al 2012;North and Fiske 2013) and demonstrated how stereotypes affect a range of different outcomes. Empiricist considerations allow us to assess ageism in as valid, reliable, and accurate a manner as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Their study demonstrates robust empirical results, a transparent description of the study design and decisions made during the research process, and a highly effective way of instantiating what prejudice, stereotyping, and discrimination corresponds to in real life situations. North and Fiske's (2013) development of an intergenerational-tension ageism scale illustrates an explicit way of assessing ageism in an empirical study. In this study, North and Fiske did not depart from a definition of ageism, but from existing ageism scales, which they felt focused mainly on descriptive stereotypes and what older people are.…”
Section: Empiricist Considerationsmentioning
confidence: 99%
See 1 more Smart Citation